Clinical and Obstetric Aspects of Pregnant Women with COVID-19: A Systematic Review - Sarah Nilkece Mesquita Araújo Nogueira Bastos; Bárbara Louise Freire Barbosa; Larisse Giselle Barbosa Cruz; Rayza Pereira de Souza; Simone Santos e Silva Melo; Caroline Camargo Bandeira da Silveira Luz (Federação Brasileira das Sociedades de Ginecologia e Obstetrícia, 2022)
Abstract Objective To analyze the clinical and obstetric aspects of pregnant women with COVID-19. Methods A systematic literature review in the MEDLINE/PubMed, LILACS, SCIELO, and CNKI databases was performed from March to May 2020, with the descriptors: Pregnancy; 2019-nCov; Coronavirus; SARS-Cov-2, Covid-19. Of those chosen were original titles, without language and period restriction and that addressed pregnant women with a clinical and/or laboratory diagnosis of COVID-19. Revisions, editorials, and duplicate titles were excluded. The Newcastle-Ottawa (NOS) and Murad et al. scales were used to assess the quality of the studies. Results We included 34 articles with 412 pregnant women infected with severe acute respiratory syndrome (SARS-Cov-2), with an average age of 27.5 years of age and 36.0 gestational weeks. The most common symptom was fever (205 [49.7%]), and 89 (21.6%) pregnant women progressed to severe viral pneumonia. Laboratory tests showed an increase in C-reactive protein (154 [37.8%]), and radiological tests showed pneumonia with peripheral ground-glass pattern (172 [51.4%]). Emergency cesarean delivery was indicated for most pregnant women, and the most common gestational complication was premature rupture of ovarian membranes (14 [3.4%;]). We detected 2 (0.5%) neonatal deaths, 2 (0.5%) stillbirths, and 1 (0.2%) maternal death. Conclusion Pregnant women with COVID-19 presented a clinical picture similar to that of non-infected pregnant women, with few obstetric or neonatal repercussions. There was a greater indication of cesarean deliveries before the disease aggravated, and there was no evidence of vertical transmission of the infection.